Superconductivity and phonon self-energy effects in Fe_{1+y}Te_{0.6}Se_{0.4} - S.-F. Wu; A. Almoalem; I. Feldman; A. Lee; A. Kanigel; G. Blumberg (Physical Review Research, 2020)
We study a Fe_{1+y}Te_{0.6}Se_{0.4} multiband superconductor with T_{c}=14K by polarization-resolved Raman spectroscopy. Deep in the superconducting state, we detect pair-breaking excitation at 2Δ=5.6meV in the XY(B_{2g}) scattering geometry, consistent with the fundamental gap energy Δ=3meV revealed by ARPES on the holelike Fermi pocket with d_{xz}/d_{yz} character. We analyze the superconductivity-induced phonon self-energy effects for the B_{1g}(Fe) phonon mode and derive the electron-phonon coupling constant λ^{Γ}≈0.026, which is insufficient to explain superconductivity with T_{c}=14K.